Историческая и национальная специфика британских легенд - Акбарова, Ч.У. (Культура народов Причерноморья, 2014)
В статье впервые читателям-гуманитариям представлены британские легенды и
классификация легенд. У статті вперше презентовано читачеві-гуманітарію британські легенди і класифікація
легенд. The paper gives the first presentation of the British legends and the classification of legends for
humanitarian audience.
Since ancient times, Great Britain has been amongst the most significant in the world for Magic, Myths, Ghosts
and Legends.
When it comes to legends, Great Britain has it all… ancient islands, steeped in ancient legends and history.
Almost every town, city and village in Britain has its own secret history.
Ghosts and hauntings… It was a natural that Britain was the setting for the hugely successful Ghostly legends.
Given its turbulent, ancient and bloody history, it is no wonder that Britain has, per square mile, the most highly
documented and recorded history of ghosts and ghostly sightings in the world. There appears to be much behind
the legends and ghostly myths also. Whilst many of the more ancient ghost stories and traditions seem to stem
directly from historical events and word of mouth, in many cases these old stories have been kept alive by
modern sightings and eyewitness accounts.